Structural basis of ligand recognition in 5‐HT3 receptors. (30th November 2012) - Kesters, Divya; Thompson, Andrew J; Brams, Marijke; van Elk, René; Spurny, Radovan; Geitmann, Matthis; Villalgordo, Jose M; Guskov, Albert; Helena Danielson, U; Lummis, Sarah C R; Smit, August B; Ulens, Chris
Abstract : The 5‐HT3 receptor is a pentameric serotonin‐gated ion channel, which mediates rapid excitatory neurotransmission and is the target of a therapeutically important class of anti‐emetic drugs, such as granisetron. We report crystal structures of a binding protein engineered to recognize the agonist serotonin and the antagonist granisetron with affinities comparable to the 5‐HT3 receptor. In the serotonin‐bound structure, we observe hydrophilic interactions with loop E‐binding site residues, which might enable transitions to channel opening. In the granisetron‐bound structure, we observe a critical cation–π interaction between the indazole moiety of the ligand and a cationic centre in loop D, which is uniquely present in the 5‐HT3 receptor. We use a series of chemically tuned granisetron analogues to demonstrate the energetic contribution of this electrostatic interaction to high‐affinity ligand binding in the human 5‐HT3 receptor. Our study offers the first structural perspective on recognition of serotonin and antagonism by anti‐emetics in the 5‐HT3 receptor. Structural basis of ligand recognition in 5‐HT3 receptors: The crystal structures of a binding protein engineered to recognize serotonin (5‐HT) and the anti‐emetic granisetron with affinities comparable to the 5‐HT3 receptor reveal important structural details of ligand recognition in the 5‐HT3 receptor.